3D-evaluation of the maxillary sinus in cone-beam computed tomography - Julia Luz; Dominique Greutmann; Daniel Wiedemeier; Claudio Rostetter; Martin Rücker; Bernd Stadlinger (SpringerOpen, 2018)
Abstract Background There are few studies measuring the dimensions of the maxillary sinus, being mostly based on computed tomography imaging and rarely being based on cone-beam computed tomography (CBCT). The aim of this study was to measure the 3D osseous and soft tissue defined volume and surface area of the maxillary sinus. Further, possible associations with patient-specific and sinus-related variables were evaluated. Methods A total of 128 maxillary sinuses in 64 patients were analyzed using cone-beam computed tomography data. Surface area and volume of the osseus maxillary sinuses as well as of the remaining pneumatized cavities in cases of obliterated sinuses were calculated by the implant planning software SMOP (Swissmeda AG, Baar, Switzerland). Further, patient-specific general variables such as age, gender, and dentition state as well as sinus-related factors including apical lesions, sinus pathologies, and number of teeth and roots communicating with the maxillary sinus were recorded. Results For osseus bordered sinuses, mean surface area was 39.7 cm2 and mean volume 17.1 cm3. For the remaining pneumatized cavities, mean surface area was 36.4 cm2 and mean volume 15 cm3. The calculated mean volume of obliterated sinuses (42.2% of all sinuses were obliterated) was 5.1 cm3. Further, an association between the obliterated volume and the presence of pathologies was detected. Male patients showed a significantly higher mean osseus volume compared to female patients. No association was apparent between a patient's age or dentition state and sinus volume, nor for communicating tooth roots and sinus pathologies or unilateral opacity and apical radiolucency. There was also no significant association between bilateral obliterated sinuses and the scan date being in autumn/winter. Conclusions The present study showed that the CBCT is suitable for the evaluation of the maxillary sinus. The implant planning software SMOP and its included volume measuring tool are valuable for the analysis of the maxillary sinus, and possible relations with the dentition can be analyzed.